(untitled) (Journal of Biochemistry, Microbiology and Biotechnology, 2025)
The Malaysian poultry industry, a significant contributor to the agricultural sector and national GDP, is increasingly challenged by antibiotic-resistant bacterial infections, particularly from Salmonella enterica serovar Typhimurium. The widespread use of antibiotics in poultry farming has driven the emergence of resistant strains, highlighting the need for alternative antimicrobial strategies. This study evaluated the characteristics and therapeutic potential of bacteriophage vB_SenS_ST10 as a biological control agent against Salmonella infections in poultry. Host range analysis revealed that vB_SenS_ST10 exhibited a narrow host range, effectively infecting only three of the thirty-two bacterial isolates tested: S. Typhimurium 8720/06, S. enterica (SCC), and S. Tennessee. Efficiency of plating (EOP) analysis indicated reduced binding efficiency for S. enterica (SCC) with an EOP value of 1.5 x 10⁻² relative to the reference strain. Biofilm inhibition assays demonstrated significant (P < 0.05) biofilm suppression at phage concentrations above 10⁴ PFU/mL, though a plateau was observed at higher levels, and complete biofilm eradication was not significantly achieved even at 10⁹ PFU/mL. Importantly, vB_SenS_ST10 did not affect beneficial gut bacteria, such as Lactobacillus and Bifidobacterium species, supporting its potential for targeted antimicrobial application without disrupting gut microbiota. The selective nature of vB_SenS_ST10, combined with its ability to inhibit biofilm formation, presents a promising approach to mitigate Salmonella-associated contamination in poultry production. However, further research is necessary to optimise its application and investigate mechanisms underlying biofilm resilience in poultry production systems.